Add-on Levetiracetam in Children With Refractory Epilepsy: A Systematic Review - Ali Abbaskhanian; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2016)
Context: Recently, new anti-epileptic drugs are marketed to be used as an add-on to the traditional drugs in children with refractory epilepsy. Levetiracetam is a second-generation of new anti-epileptic drugs with unknown precise mechanism of action in brain and synaptic vesicle in children with drug resistant epilepsy. Herein, the efficacy and safety of add-on levetiracetam in children with refractory epilepsy is reviewed. Evidence Acquisition: A literature review was performed on efficacy and safety of add-on Levetiracetam in children with refractory epilepsy using international databases with the following terms: levetiracetam, refractory epilepsy, drug resistant epilepsy, seizures/epilepsy, children/pediatric. All articles related to add-on levetiracetam in children with refractory epilepsy written in English and published from 2000 to 2015 were included. The title and abstracts of 542 articles were assessed, of which, 488 were excluded. The full texts of the other 54 articles were assessed for relevance. Results: Of the nine eligible articles, 1036 patients aged ≤ 18 years were identified. Male patients (52%) were more prominent than female ones. Five articles reported that levetiracetam therapy appeared more effective against localization-related than generalized epilepsy. The dosage of levetiracetam ranged from 6 to 70 mg/kg/day, with a mean of 43.2 mg/kg/day based on the mean doses reported by four of nine reviewed articles. The mean duration of follow-up was 39 weeks (ranging from 8 - 144 weeks). Administration of levetiracetam was effective in 42.24% of the patients (responders with >50% decrease in seizure frequency), of whom 11.8% had become seizure free. The mean number of anti-epileptic drugs tried before introducing levetiracetam treatment was 4.4 (ranging 1 - 20). The most frequent side effects were psychological and behavioral changes (11.1%), followed by agitation (9.2%) and sleep disturbances (6.7%). Conclusions: The current review demonstrated that levetiracetam, as an add-on therapy, is an effective and well-tolerated anti-epileptic drug, associated with reversible and no serious side effects, to control seizure frequency of childhood refractory epilepsy.